The Differences Of Cerebral, Abdominal, And Renal Oxygenation In Neonates With Hypothermia And Post-Rewarming Using Nirs At Dr. Soetomo Hospital - Dwi Lestari Avianti; Martono Tri Utomo; Risa Etika (Green Publisher Indonesia, 2026)
Background: Hypothermia significantly affects survival in neonates, as their thermoregulation is less effective than in older children and adults. Hypothermia can worsen metabolic processes, leading to hypoglycemia, hypoxia, and metabolic acidosis. Near infrared spectroscopy (NIRS) is useful for assessing regional tissue oxygenation (RSO2), providing insights into the oxygen supply and demand balance in vulnerable organs. Objective: This study aims to demonstrate differences in cerebral, abdominal, and renal tissue oxygenation in neonates under hypothermia and after rewarming using NIRS. Methods: An observational cross-sectional study was conducted from November 2019 to January 2020 at the NICU of Dr. Soetomo Surabaya Hospital. Neonates were divided into hypothermia, rewarming, and normothermic groups. NIRS assessments were performed during hypothermia and post-rewarming. Statistical analyses were conducted using paired t-tests or Wilcoxon tests for the hypothermia group, and independent t-tests or Mann-Whitney tests for comparisons between hypothermia and normothermic groups, with a significance level of p < 0.05. Results: A total of 106 neonates met the criteria: 51 in the hypothermia and rewarming group and 55 in the normothermic group. The average birth weight was 2261.96 ± 832.26 grams for the hypothermia group and 2009.09 ± 676.87 grams for the normothermic group. Significant differences were noted in heart rates and renal tissue oxygenation (RrSO2) between conditions, with p-values of 0.014 and 0.023, respectively. Conclusion: This study found significant differences in renal tissue oxygenation between hypothermic conditions and post-rewarming.